An integrated multidisciplinary algorithm for the management of spinal metastases: an International Spine Oncology Consortium report. Issue 12 (December 2017) - Spratt, Daniel E; Beeler, Whitney H; de Moraes, Fabio Y; Rhines, Laurence D; Gemmete, Joseph J; Chaudhary, Neeraj; Shultz, David B; Smith, Sean R; Berlin, Alejandro; Dahele, Max; Slotman, Ben J; Younge, Kelly C; et al.
Summary: Spinal metastases are becoming increasingly common because patients with metastatic disease are living longer. The close proximity of the spinal cord to the vertebral column limits many conventional therapeutic options that can otherwise be used to treat cancer. In response to this problem, an innovative multidisciplinary approach has been developed for the management of spinal metastases, leveraging the capabilities of image-guided stereotactic radiosurgery, separation surgery, vertebroplasty, and minimally invasive local ablative approaches. In this Review, we discuss the variables that should be considered during the management of these patients and review the role of each discipline and their respective management options to provide optimal care. This work is synthesised into a practical algorithm to aid clinicians in the management of patients with spinal metastasis.